Description of a polar molecular liquid in a disordered microporous material with activating chemical groups by a replica RISM theory - Hirata, F.; Kovalenko, A. (Condensed Matter Physics, 2001)
We develop a replica generalization of the reference interaction site model (replica RISM) integral equation theory to describe the structure and thermodynamics of a polar molecular liquid sorbed in a quenched disordered porous matrix including polar chemical groups. It provides a successful approach to realistic models of molecular liquids, and properly allows for the effect of a quenched disordered medium on the sorbed liquid. The description can be readily extended to a mobile liquid comprising a mixture of ionic and polar molecular species. The replica RISM integral equations are complemented by the HNC closure and its partial linearization (PLHNC), adequate to ionic and polar molecular liquids. In these approximations, closed expressions for the excess chemical potentials of the quenched-annealed system are derived. We extend the description to the case of soft core interaction potentials between all species of the quenched-annealed system, in which the liquid and matrix equilibrium distributions are characterized in general by two different temperatures. The replica RISM/PLHNC-HNC theory is applied to water sorbed in a quenched matrix roughly modelling porous carboneous material activated with carboxylic (-COOH) groups. The results are in qualitative agreement with experiment for water confined in disordered materials.